Studying direct and indirect effects of impulses in powered aero-gravity-assist maneuvers around venus - Murcia, J. O.; Prado, A. F.B.A.; Gomes, V. M. [UNESP] (My University, 2018)
The study of aero-gravity-assisted maneuvers around Venus is the focus of the present paper. These are maneuvers that combine the passage by the gravity field of the planet with an impulsive maneuver that is applied at the moment of the closest approach around Venus, and the modification of the trajectory is made by lift and drag. This option gives new possibilities for the maneuver, which can vary the angle of curvature, the energy and the inclination of the spacecraft. The paper also studies the direct and the indirect effects of the application of an impulsive maneuver. This is done by measuring the effects of each individual force present in the dynamics, by the integration of the accelerations coming from those forces.
Keywords: Celestial mechanics; Planets; Satellites: atmospheres; Space vehicles